SET-promoted photoaddition reactions of fullerene C60 with tertiary N-trimethylsilylmethyl substituted α-aminonitriles. Approach to the synthesis of fulleropyrrolidine nitriles. Issue 44 (2nd November 2017) - Lim, Suk Hyun; Cho, Dae Won; Choi, Jungkweon; An, Hyunjun; Shim, Jun Ho; Mariano, Patrick S.
Abstract: Photoaddition reactions of C60 with tertiary N -arylmethyl- N -trimethylsilylmethyl substituted α-aminonitriles were explored. The results show that these photoreactions produce both trimethylsilyl- and cyano group containing fulleropyrrolidines as major products through pathways involving 1, 3-dipolar cycloaddition of azomethine ylide intermediates. The ylides are formed either by SET from α-aminonitriles to the triplet excited state of C60 (in N2 -purged solutions) followed by desilylation or deprotonation, or by hydrogen atom abstraction by singlet oxygen (in O2 -purged solutions). In contrast, photoreactions of C60 with analogous amines that do not contain trimethylsilyl group form fulleropyrrolidines that contain aryl- and cyano substitutents on the pyrrolidine ring. The efficiencies of these photoaddition reactions are influenced by several factors including reaction condition (N2 or O2 -purged), solvent polarity, the electronic and structural nature of α-aminonitriles and additive. The presence of trimethylsilyl group in the α-aminonitrile substrates plays a crucial role in enhancing the efficiencies of the fulleropyrrolidine forming reactions. Graphical abstract: